2021
DOI: 10.1093/jn/nxaa331
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Choline Modulates Growth Performance and Gut Inflammation by Altering the Gut Microbiota and Lipid Metabolism in Weaned Piglets

Abstract: Background Whether dietary choline and bile acids affect lipid use via gut microbiota is unclear. Objectives This study aimed to investigate the effect of choline and bile acids on growth performance, lipid use, intestinal immunology, gut microbiota, and bacterial metabolites in weaned piglets. Methods A total of 128 weaned piglets [Duroc × (Landrace × Yorksh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
1
21
1
Order By: Relevance
“…Choline is a metabolite produced from phosphatidylcholine by some gut microbes with phospholipase D enzymes, which plays an important role in maintaining the structural integrity of cell membranes (17,66,67). Studies have shown that choline supplementation helps maintain intestinal mucosal immune homeostasis and strengthens the intestinal barrier (68). Here, MOP reversed the DSS-induced disturbance of lipid metabolite levels and had a tendency to promote choline increases.…”
Section: Discussionmentioning
confidence: 90%
“…Choline is a metabolite produced from phosphatidylcholine by some gut microbes with phospholipase D enzymes, which plays an important role in maintaining the structural integrity of cell membranes (17,66,67). Studies have shown that choline supplementation helps maintain intestinal mucosal immune homeostasis and strengthens the intestinal barrier (68). Here, MOP reversed the DSS-induced disturbance of lipid metabolite levels and had a tendency to promote choline increases.…”
Section: Discussionmentioning
confidence: 90%
“…The chyme digestive enzyme activities were not affected by the two acidifiers, which was inconsistent with the previous report [ 45 ]. This discrepancy might be due to the different animal species, physiological stages, dietary structure, and composition of acidifiers [ 38 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the gut microbiota has attracted increasing attention, and the gut microbiota is closely related to livestock and poultry production performance [ 19 , 20 , 21 , 22 ], nutritional metabolism [ 15 , 23 ], and immune function [ 24 , 25 ]. Predecessors found through the technique of faecal microbiota transplantation that the growth performance of calves after faecal microbiota transplantation was significantly increased [ 21 ], which shows that the growth performance of gut microbiota is improved, but the mechanism of action is still unclear.…”
Section: Introductionmentioning
confidence: 99%